2004
DOI: 10.1080/00498250412331285436
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the novel canine CYP1A2 1117 C>T SNP causing protein deletion

Abstract: 1. The pharmacokinetics of YM-64227 (4-cyclohexyl-1-ethyl-7-methylpyrido[2,3-d]-pyrimidine-2-(1H)-one), a novel and selective phosphodiesterase type 4 inhibitor, was characterized in beagle dogs. Based on the plasma parent drug to major hydroxylated metabolite ratio, 21 dogs were phenotyped as 16 extensive metabolizers (EM) and five poor metabolizers (PM).2. Nucleotide sequences of CYPs 1A2, 2B11, 2C21, 2D15, 2E1 and 3A12 were investigated in the EM and PM dogs. A CYP1A2 1117 C>T single nucleotide polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 22 publications
3
34
0
Order By: Relevance
“…A list of identified breed-specific idiosyncrasies that can influence drug absorption and metabolism are provided in Tables III and IV ( [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Table III includes recognized metabolic idiosyncrasies and Table IV includes physiologic idiosyncrasies.…”
Section: Breed-related Differences In Pharmacokinetics and Pharmacodymentioning
confidence: 99%
“…A list of identified breed-specific idiosyncrasies that can influence drug absorption and metabolism are provided in Tables III and IV ( [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Table III includes recognized metabolic idiosyncrasies and Table IV includes physiologic idiosyncrasies.…”
Section: Breed-related Differences In Pharmacokinetics and Pharmacodymentioning
confidence: 99%
“…The canine liver microsomes were prepared and the CYP1A2 1117 CϾT SNP genotyping method was performed as described by Tenmizu et al (2004a). YM-64227 (5 M) was incubated in a reaction mixture (0.5 ml) consisting of 0.1 mg/ml liver microsomes, a NADPH-generating system (1.3 mM NADP, 3.3 mM glucose 6-phosphate, 0.4 U/ml glucose-6-phosphate dehydrogenase, and 3.3 mM MgCl 2 ), 0.1 mM EDTA, and 100 mM Na/K-phosphate buffer (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, a novel CYP1A2 1117 CϾT single nucleotide polymorphism (SNP) was found in beagle dogs, which are used extensively in pharmacology and safety assessment studies (Tenmizu et al, 2004a;Mise et al, 2004a). This SNP resulted in an amino acid change from an Arg codon to a stop codon at position 373, yielding an inactive enzyme.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, CYP1A2 polymorphisms in the coding region are rare and only occasionally appear to decrease enzyme activity (Faber et al, 2005). A CYP1A2 polymorphism in beagle dogs has been reported (Tenmizu et al, 2004). The mutation is a single nucleotide polymorphism, CYP1A2 1117 CϾT, which results in an amino acid change from arginine to an early stop codon at position 373 (truncated inactive protein).…”
Section: Introductionmentioning
confidence: 99%